RES155 : Economics for built environment / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2023)
The course introduces the basic principles of both microeconomics and macroeconomics and to relate these principles to the built environment. The emphasis is on the nature and functions of the price mechanism and market structures. Theories of production, distribution and consumption are also introduced with relevant applications from the built environment. In macroeconomics, it will cover topics relating to national income, inflation and unemployment, and banking and money supply.